Charcoal Amendment Enhances Sorghum Yield and Biomass Production: A Sustainable Approach to Improved Crop Performance. (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Field experiment was conducted during the 2024 rainy season at the Teaching and Research Farm, Faculty of Agriculture, Bayero University Kano (BUK), and the National Horticultural Research Institute (NIHORT), Bagauda, to assess the effect of charcoal on the growth and yield of sorghum. Four charcoal application rates (0, 5, 10, and 15 t/ha) were arranged in a randomized complete block design with three replications. Results of the study indicated that charcoal application significantly (p